Properties and Behavior of Soil Online Lab Manual - Hossain, Sahadat; Islam, Azijul; Badhon, Faria Fahim (Open textbook library., 2021)
This project aims to provide a complete guide for the CE/AREN 3143 course (Properties and Behavior of Soil). Students will be benefitted from this online lab manual.